Staurosporine resistance in inflammatory neutrophils is associated with the inhibition of caspase- and proteasome-mediated Mcl-1 degradation. Issue 1 (26th August 2015) - Hornstein, Tamara; Lehmann, Sarah; Philipp, Denise; Detmer, Susanne; Hoffmann, Michèle; Peter, Christoph; Wesselborg, Sebastian; Unfried, Klaus; Windolf, Joachim; Flohé, Sascha; Paunel-Görgülü, Adnana
Abstract : Triggering of Mcl-1 degradation by Akt inhibition may overcome neutrophil intrinsic apoptosis resistance, and help reduce excessive inflammation in inflammatory diseases. Abstract: Apoptosis resistance in activated neutrophils is known to be associated with collateral damage of surrounding tissue, as well as immune and organ dysfunction. Thus, the safe removal of neutrophils by apoptosis induction represents a prerequisite for the resolution of inflammation. Here, we report that intrinsic apoptosis resistance in human neutrophils, isolated from severely injured patients, is based on enhanced stabilization of antiapoptotic myeloid cell leukemia 1 and subsequent impairment of downstream apoptotic pathways. Whereas extrinsic apoptosis induction by the activation of Fas death receptor on inflammatory neutrophils was accompanied by caspase- and proteasome-mediated myeloid cell leukemia 1 degradation, intrinsic apoptosis induction by staurosporine led to a significant stabilization of myeloid cell leukemia 1 protein, which impeded on truncated forms of B cell lymphoma 2-associated X protein and B cell lymphoma 2 homology domain 3-interacting domain death translocation and subsequent cytochrome c release from the mitochondria. We show further that profound inhibition of myeloid cell leukemia 1 degradation is based on the inhibition of caspases and sustained activation of kinases involved in cell survival, such as Akt. Accordingly, impeded myeloid cell leukemia 1 phosphorylation on Ser159 by glycogen synthase kinase 3 and protein ubiquitination has been demonstrated. Inhibition of myeloid cell leukemia 1 activity markedly increased sensitivity to staurosporine-induced cell death. Altogether, these results provide new insights into the mechanisms underlying myeloid cell leukemia 1-mediated apoptosis resistance to staurosporine under inflammatory situations and should be considered for the development of novel therapeutic strategies.